Booklet with a series of 50 photos of the battle at the river Ebro: Preparation for the offensive; the Brigade attacking and defensing at the bend of the Ebro; adieu. Several group portraits. André Marty amid Scandinavian comrades of the 42th battalion
Booklet with a series of 50 photos of the battle at the river Ebro: Preparation for the offensive; the Brigade attacking and defensing at the bend of the Ebro; adieu. Several group portraits. André Marty amid Scandinavian comrades of the 42th battalion.